Perancangan dan Pengembangan Bed Shower Menggunakan Metode Quality Function Deployment (QFD) Berdasarkan Prinsip Ergonomi - Ayi Fitriani; Hari Purnomo (Universitas Serang Raya, 2018)
This research was conducted to design a bed shower and study the design and development of a bed shower for patient needs. The purpose of creating a bed shower is because of the lack for these tools to make it easier for nurses to bathe patients who are paralyzed or unable to move their limbs. The method used in this study uses the measurement parameters of the Quality Function Deployment (QFD) method. The results of the study obtained lightly designed tools that were the priority. The next variable that is considered is ergonomic, durable, comfortable to use and clean, and finally, the price is affordable. The design of the bed shower pays more attention to the principle of ergonomics by paying attention to the material used. Bed shower designed with three dimensions using Solid Work software with the translation of the concept that consumers want is realized by providing trolley wheels and bath pads that are easily dry and easily folded and carried. While the size of the tool with a length of 216 cm, width of 60 cm, trolley height of 107 cm, width of the trolley of 29 cm, display tools that are easy and practical, easy to clean allow tools to be separated, have durable durability with an estimate of more than 5 years , having a cheap price is around Rp. 5,000,000, - by making selected materials and maximizing the function of one pump.